Sports injuries sourcebook : basic consumer health information about sprains, fractures, tendon injuries, overuse injuries, and injuries to the head, spine, shoulders, arms, hands, trunk, legs, knees, and feet, and facts about sports- specific injuries, injury prevention, protective equipment, children and sports, and the diagnosis, treatment, and rehabilitation of sports injuries ... - Larsen, Laura (Detroit, MI : Omnigraphics, 2012)
"Provides basic consumer health information about sports injuries in various parts of the body, protective equipment and preventive measures, treatment options, and a special section on sports injuries in children and teens. Includes index, glossary of related terms, and other resources"--
Part 9: Diagnosis, Treatment, And Rehabilitation Of Sports Injuries: -- Chapter 48: Imaging and diagnostic tests: -- 48-1: Arthrogram -- 48-2: Bone scan -- 48-3: Computed Tomography (CT) scan -- 48-4: Magnetic Resonance Imaging (MRI) -- 48-5: Ultrasound -- Chapter 49: Medications for sports injuries: -- 49-1: Medications to treat sports-related injuries -- 49-2: Injections for pain management -- Chapter 50: Specialized surgical treatments and therapy: -- 50-1: Arthroscopic surgery -- 50-2: Meniscal repair -- 50-3: ACL repair -- 50-4: Cartilage transfer -- 50-5: Physical therapy -- Part 10: Sports Injuries In Children And Young Athletes: -- Chapter 51: Children and sports injuries: -- 51-1: Sport and recreation safety for children -- 51-2: Playground injuries -- Chapter 52: Sports physicals -- Chapter 53: Preventing children's sports injuries -- Chapter 54: Overtraining burnout in young athletes -- Chapter 55: Preventing child abuse in youth sports -- Chapter 56: Growth plate injuries -- Chapter 57: Developmental diseases and sports injuries: -- 57-1: Osgoog-Schlatter disease -- 57-2: Sever's disease -- Chapter 58: Return to play: -- 58-1: Return to play issues -- 58-2: Mentally preparing athletes to return to play -- Part 11: Additional Help And Information: -- Chapter 59: Glossary of terms related to sports injuries -- Chapter 60: Directory of resources related to sports injuries -- Index.
Includes bibliographical references and index.
Keywords: Sports injuries; Sports medicine; Wounds and injuries; Athletic Injuries -- Resource Guides; Sports medicine -- Resource Guides; Sports injuries; Sports medicine; Wounds and injuries